THE POLICY OF WOMEN’S AND CHILDREN’S EMPOWERMENT IN ACEH (An Analysis of the Aceh Qanun on Women’s Empowerment and Children’s Protection) - Anita T. Iskandariata (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2018)
Women's struggle through policy advocacy is an emerging strategy among women’s movements in post-conflict and post-tsunami Aceh. Policy advocacy has been viewed as a strategic entrance to create an equal development for women and men. Before and after the tsunami, women and children in the area have been in a subordinate position in which they have not got their rights of justice and equality. Looking at the existing women’s conditions as described above, the women’s Empowerment Bureau (Biro PP) viewed the importance of initiating a regulation ensuring women’s right’s and children ‘s protection.  Biro PP  (now BP3A) submitted Draft of Women’s Empowerment and Protection Qanun or Qanun Pemberdayaan dan Perlindungan Perempuan (QPP) and the draft of Child Protection Qanun or Qanun Perlindungan Anak (QPA). After several years, since the Qanun initiated, it has not been implemented as a regulation for empowering and protecting women’s rights. It is believed that the efforts to achieve gender equality and equity in Aceh will be accelerated if QPP and QPA are implemented with strong support from all social elements in the area. The successful implementation of QPP and QPA depends on the capacity of BPPPA a governmental leading sector that having a mandate on women’s empowerment and children’s rights protection.